Pre-clinical evaluation of a P. berghei-based whole-sporozoite malaria vaccine candidate. (December 2018) - Mendes, António; Reuling, Isaie; Andrade, Carolina; Otto, Thomas; Machado, Marta; Teixeira, Filipa; Pissarra, Joana; Gonçalves-Rosa, Nataniel; Bonaparte, Dolores; Sinfrónio, João; Sanders, Mandy; Janse, Chris; et al.
Abstract Whole-sporozoite vaccination/immunization induces high levels of protective immunity in both rodent models of malaria and in humans. Recently, we generated a transgenic line of the rodent malaria parasiteP. berghei (Pb ) that expresses theP. falciparum (Pf ) circumsporozoite protein (Pf CS), and showed that this parasite line (Pb Vac) was capable of (1) infecting and developing in human hepatocytes but not in human erythrocytes, and (2) inducing neutralizing antibodies against the humanPf parasite. Here, we analyzedPb Vac in detail and developed tools necessary for its use in clinical studies. A microbiological contaminant-free Master Cell Bank ofPb Vac parasites was generated through a process of cyclic propagation and clonal expansion in mice and mosquitoes and was genetically characterized. A highly sensitive qRT-PCR-based method was established that enablesPb Vac parasite detection and quantification at low parasite densities in vivo. This method was employed in a biodistribution study in a rabbit model, revealing that the parasite is only present at the site of administration and in the liver up to 48 h post infection and is no longer detectable at any site 10 days after administration. An extensive toxicology investigation carried out in rabbits further showed the absence ofPb Vac-related toxicity. In vivo drug sensitivity assays employing rodent models of infection showed that both the liver and the blood stage forms ofPb Vac were completely eliminated by Malarone® treatment. Collectively, our pre-clinical safety assessment demonstrates thatPb Vac possesses all characteristics necessary to advance into clinical evaluation. Malaria: Pre-clinical characterization of transgenic malaria vaccine Pb Vac is a transgenic malaria parasite expressing circumsporozoite antigen from the human parasitePlasmodium falciparum .Pb Vac elicits neutralizingP. falciparum antibodies and can infect human hepatocytes but not erythrocytes, suggesting that humans would be non-permissive. Miguel Prudêncio and colleagues at the Institute of Molecular Medicine in Lisbon perform a detailedin vivo analysis and toxicology ofPb Vac. Extensive biodistribution analysis using a highly sensitive qPCR in non-permissive rabbit hosts showsPb Vac are present at the initial bite site early on with later appearance in the liver, but by day 10 is undetectable. Importantly noPb Vac could be detected in the blood at any time-point.Pb Vac was well tolerated with no apparent pathological signatures. In permissive mouse hostsPb Vac could be effectively eliminated from both the blood and liver and could thereby act as a potential clinical 'safety net' in the event of an erythrocytic stage or persistence in the liver.